The Identification of Persuasive Educational Message About Covid-19 Issue in New Media - Mutia Rahmi Pratiwi; Kheyene Molekandella Boer; Teddy Dyatmika; Amida Yusriana (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2021)
Indonesia has becoming one of the countries with highest rate in Covid-19 transmission and part of 15 biggest countries in the world with highest death rate because of it. Various efforts have been conducting to persuade people such as delivering the Covid-19 education messages by new media TikTok. This research is a qualitative research with content analysis as the method. The object choosen are three video in new media TikTok that come from the point of view of the health workers, family of the health workers and society. The theory used is The Persuasive Theory. The results show that the persuasive carried out through the research object used an evidence-based approach, using humor and based on diction. Based on diction is carried out from the side of the health worker family members. Based on the evidence is carried out from the point of view of people affected by the virus. The humor approach is carried out from the perspective of medical personnel. The message structure contained in the video object shows uniformity, including the presentation of messages consisting of one-sided, the order in which the message is presented using the climax flow and drawing conclusions that indicate the message is expressed or addressed directly.